Population Structure and Antimicrobial Resistance of Invasive Serotype IV Group B Streptococcus, Toronto, Ontario, Canada - Teatero, Sarah (Emerg Infect Dis, 2015)
We recently showed that 37/600 (6.2%) invasive infections with group B Streptococcus (GBS) in Toronto, Ontario, Canada, were caused by serotype IV strains. We report a relatively high level of genetic diversity in 37 invasive strains of this emerging GBS serotype. Multilocus sequence typing identified 6 sequence types (STs) that belonged to 3 clonal complexes. Most isolates were ST-459 (19/37, 51%) and ST-452 (11/37, 30%), but we also identified ST-291, ST-3, ST-196, and a novel ST-682. We detected further diversity by performing whole-genome single-nucleotide polymorphism analysis and found evidence of recombination events contributing to variation in some serotype IV GBS strains. We also evaluated antimicrobial drug resistance and found that ST-459 strains were resistant to clindamycin and erythromycin, whereas strains of other STs were, for the most part, susceptible to these antimicrobial drugs.